A LINE‐1–encoded reverse transcriptase–dependent regulatory mechanism is active in embryogenesis and tumorigenesis. (13th January 2015) - Spadafora, Corrado
Abstract : LINE‐1 (long interspersed nuclear elements) retrotransposons constitute a large family of retrotransposable elements, accounting for 17% of the human genome. They encode proteins required for their own mobilization, including a reverse transcriptase (RT) enzyme highly expressed in mouse embryos and mouse and human cancer cells and repressed in somatic differentiated healthy cells. We have found that reverse transcription takes place in early murine embryos, yielding an increase in LINE‐1 copy number during preimplantation development, which also occurs in tumor progression. RT inhibition irreversibly arrests embryo development, reduces cancer cell proliferation, promotes differentiation, antagonizes tumor growth, and causes a global reprogramming of transcription profiles. These results strongly suggest that a previously unrecognized RT‐dependent regulatory mechanism operates during preimplantation development, is repressed during differentiation to normal tissues, and, when erroneously reactivated in adult life, promotes cell transformation and cancer progression by "resurrecting" embryonic transcriptional pathways. The RT‐dependent mechanism emerges as a major source of genetic and epigenetic changes with physiological, pathological, and evolutionary implications.